The essence and necessity of developing family entrepreneurship in agriculture - Sharofova Saida Alimurat kizi; Khujakulova Nigora Rustamovna (THE INNOVATION ECONOMY, 2026)
This article is devoted to the study of the theoretical foundations of family entrepreneurship in agriculture. The development of family entrepreneurship in the agricultural sector of Uzbekistan and its significance are considered, as well as the problems arising in this area and ways to solve them. The article analyzes the economic, social and environmental aspects of family entrepreneurship, determines its role in ensuring sustainable development and well-being of the population in rural areas. The article also considers the necessary policy and practical measures to support family entrepreneurship in agriculture.